Effect of solvents extraction on phytochemical components and biological activities of Tunisian date seeds (var. Korkobbi and Arechti) - Amira Thouri (BMC Complementary and Alternative Medicine, 2017)
Abstract Background The interest in natural antioxidants, especially polyphenols, is growing more and more thanks to their positive contribution to human health. Thus, the prevention from the harmful action of oxidative stress which has been involved in many diseases such as cancer, inflammation diabetes, and cardiovascular illness. Recent research proved the bioactive compounds richness of date seeds which could be a good biological matrix of natural antioxidants. Unfortunately, an important quantity of Tunisian dates seed is discarded yearly. Methods In this study, different solvents extraction (water, methanol, absolute acetone and aqueous acetone 80%) were used and the evaluation of its effect on phytochemical level, in vitro antioxidant activities, in vitro hyperglycemia key enzymes inhibition and in vivo anti-inflammatory proprieties were established for Tunisian date seeds. Results The result revealed that the polar solvent exhibited the highest amount of bioactive compounds. The correlation between polyphenol compounds and the antioxidant potentiality explains the powerful effect of used polar solvents on inflammation, TBARS and hyperglycemia inhibition. Furthermore, it showed its higher capacity to scavenge radicals. Conclusions Therefore, this big waste of Tunisian seeds could be used as cheap source of natural antioxidant compounds which are considered as a health challenge for the poor countries.